Core SWING advanced programming - TOPLEY, KIM (Prentice Hall PTR core series., 1999)
8329B-3 The experienced developer's guide to the Swing classes! Core Swing helps you deliver the sophisticated Java GUI applications your users demand-with Java Swing techniques that start where other books leave off! Building on his bestseller Core Java Foundation Classes, Kim Topley takes on the toughest Swing issues raised by programmers throughout the Java community and addresses crucial topics first-generation Swing books completely missed. With Core Swing , you'll discover how to exploit the Swing tree and table controls to the fullest, customize and create your own text fields with features that sophisticated users expect, build your own editors and file viewers, and much more. There is complete and in-depth coverage of Swing's HTML support, a topic barely addressed in other Swing books. You'll also find detailed coverage of undo/redo and drag-and-drop, with lengthy, fully documented code examples, in the book and on the accompanying CD-ROM. Every Core Series book: DEMONSTRATES how to write commercial quality code FEATURES dozens of nontrivial programs and examples-no toy code! FOCUSES on the features and functions most important to real developers PROVIDES objective, unbiased coverage of cutting-edge technologies-no hype! Core Swing: Advanced Programming delivers: State-of-the-art insights into the Swing classes that other books can't touch Practical techniques for building the Swing components you really need Fast-track techniques for making the most of text controls, editors, tables, and drag-and-drop Hundreds of professional-level code examples CD-ROM The accompanying CD-ROM includes all of the book's detailed code examples a bonus chapter taken from Kim Topley's first book, Core Java Foundation Classes, and trial versions of SwingBuilder from SwingSoft and Netbeans.